Principles of model checking - Baier, Christel; Katoen, Joost-Pieter (MIT Press, 2008)
A comprehensive introduction to the foundations of model checking, a fully automated technique for finding flaws in hardware and software; with extensive examples and both practical and theoretical exercises.